Formação crítico-reflexiva de professoras-alfabetizadoras mediada pela leitura da obra A fada que tinha ideias - Coelho, Taciana Oliveira Carvalho (2011)
This study aims to describe and interpret the phenomenon critical-reflective education of literacy teachers mediated by the reading of the children s literature book A fada que tinha ideias [The fairy who had ideas] (Almeida, 1976). The objective is to give a contribution of social relevance to the transformation of those teachers pedagogical practice. Theoretical constructs about teachers criticalreflective education, as suggested by Ghedin (2002), Perrenoud (2002), Schön (2000), Freire, P. (1970/1984, 2002), Dewey (1933/1959), among others, are discussed and the children's literature book is the trigger element of the critical reflection proposed. Among the various methodological options available for research in Applied Linguistics, I discovered an innovative and attractive interpretive path in the hermeneutic-phenomenological approach (van Manen, 1990; Ricoeur, 1976, 2001; Freire, M.M., 2010, 2007a, 2007b, 1998). The experience of reading and reflecting about the book was registered in texts produced by 55 participants of Letra Viva Alfabetização, a program for literacy teachers, which is offered by the Municipal Department of Education in a city of Vale do Paraíba region, in the state of São Paulo. Based on the textualization, thematization and validation processes proposed by van Manen (1990) and also on refinement and re-signification movements proposed by Freire, M.M. (2010, 2009, 2008a, 2007a, 2006), it was possible to identify five hermeneutic-phenomenological themes that constitute the structure of the investigated phenomenon, as presented in this thesis